Managing Policy: Executive Agencies of the European Commission - Institut für Höhere Studien (IHS), Wien (2017)
Abstract: 'Agencification' in the European Union has emerged as as important reseach topic at the intersection between political science and organizational studies. This Working Paper focuses on a group of six agencies under the wings of the European Commission that is often overlooked in the literature, despite the fact that these agencies are now set up for more than a decade, and despite the fact that their portfolio is growing. It sheds light on the historical context of their establishment and their legal foundation, looks at their organizational structure, and investigates the fields of action in which they are tasked to operate